Felvidékről Pitvarosra telepített magyarok a Szegedi Népbíróság előtt : 1946-1949 - Miklós, Péter (Közép-Európai Közlemények, 2011)
Pitvaros is a village in Csongrád County, Hungary (the part of historical Csanád County), founded by slovakians in 1816. In the second part of 1940’s the local slovakians’ great mass have migrated to Czechoslovakia and theirs place –the Hungarian and Czechoslovakian Government commonly –settled hungarians from the Hungarian Uplands (from Gúta, Vágfarkasd etc. villages). In this study the author demonstrates: there was an compound –ethnical, confessional and political –conflict between the hungarian settlers and the old resident slovakians in Pitvaros. The sources of this essay was the People’s Tribunal of Szeged’s archives. The author presents by typical People’s Tribunal legal actions the problems and conflicts of hungarian–slovakian symbiosis in South-Hungary after the czechoslovakian–hungarian polulation exchange (1946–1949).